Towards the Elimination of Pediatric HIV: Enhancing Maternal, Sexual, and Reproductive Health Services - Alana F. Hairston, MSc; Emily A. Bobrow, PhD, MPH; Christian S. Pitter, MD, MPH (International Journal of Maternal and Child Health and AIDS, 2016)
Almost 10 years ago, the United Nations adopted a comprehensive, four-pronged approach for the prevention of mother-to-child transmission of HIV (PMTCT). Despite all four prongs being central to the elimination of pediatric HIV, and the health of the mother being critical to reaching this goal, PMTCT programs have historically focused more attention on preventing HIV transmission from mother to child (prong 3) than on preventing HIV in women of reproductive age (prong 1) and preventing unintended pregnancies in women living with HIV (prong 2). In this commentary, experts from the Elizabeth Glaser Pediatric AIDS Foundation (EGPAF) argue that within the context of efforts to eliminate pediatric HIV, there are many ways to keep women living with HIV alive and at the center of the response to the global epidemic. One of the ways to do this is to enhance maternal and sexual and reproductive health (SRH) services. Within the elimination agenda, integration and linkages between PMTCT and comprehensive SRH services can keep mothers alive and at the center of the response. The commentary highlights some of the foundation’s global health work supporting, evaluating and enhancing maternal and SRH services provided to women living with HIV and proposes concrete actions for donors, researchers, policy makers and program implementers to further enhance maternal and SRH services within the context of PMTCT. If keeping women living with HIV is an integral component of the elimination of pediatric HIV agenda, maternal and SRH research, policies and programs need to be strengthened within the context of PMTCT. Donor funding and priorities for PMTCT also need to be more supportive of primary prevention of HIV infection among women of childbearing age and preventing unintended pregnancies among women living with HIV.